New Powers: How to become one and how to manage them, de Amrita Narlikar - Stuenkel, Oliver (Meridiano 47 - Journal of Global Studies, 2017)
Dr. Amrita Narlikar, who teaches International Politics at Cambridge University, has written a very short and elegant book about Brazil’s, India’s and China’s rise. The topic of emerging powers invites, quite naturally, a lot of forward-looking analysis. The now famous paper “Dreaming with the BRICs: The Path to 2050”³, published by Goldman Sachs in 2003, offers a seemingly unending number of fascinating discussions, all based on the question of how the world will look like when the five greatest economies are, in that order, China, the United States, India, Japan and Brazil. Will rising powers integrate into today’s world order, or will they overthrow the current system? Yet Dr. Narlikar resists the temptation of participating in the guessing game and takes a sober look into the past, analyzing India’s, China’s and Brazil’s international negotiation strategies to answer the question mentioned above. She argues that “at one extreme, we may expect the new power to show complete socialisation. At the other extreme, however, we may also see the new power using its newfound status to pursue alternative visions of world order.” This issue already matters greatly today, for Narlikar rightly contends that today’s rising powers, while not yet well-integrated into international institutions, have acquired the de facto status os veto players “whose agreement is required for a change of the status quo.” This has important implications for the stability of today’s world order. If rising powers fail to assume global responsibility, established powers such as the United States may soon no longer be able to provide the global public goods that define today’s global order.